STRUCTURE AND SIGN MEANING OF HANG WOJA CEREMONY (HARVEST THANKSGIVING) IN LENTO VILLAGE, POCORANAKA SUB-DISTRICT, MANGGARAI REGENCY - Ikin, Mariana; Martono, Boedi; Sugiyanto, Iwan (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2022)
The Teing Hang Woja ceremony is an annual event held in August to express gratitude for a bountiful harvest. This study aims to describe the structure and meaning of the ceremony in Lento village, Poco Ranaka sub-district, East Manggarai district. Using a qualitative approach and descriptive method, the author collected data from the customary leader of Lento village through interviews, observations, and documentation. The data was analyzed through reduction, presentation, transcription, and conclusion drawing. The study concludes that the Hang Woja ceremony is a form of gratitude for a successful harvest.